A novel total synthesis of aculeatin A via a stepwise approach. Issue 16 (2nd February 2017) - Zhang, Zhibin; Leng, Xiao; Yang, Shenkun; Liang, Cheng; Huang, Shuangping; Wang, Xiaoji
Abstract : Aculeatin A, isolated from the plant Amomum aculeatum, is a dispirocyclic compound having antimalarial activity. We describe a novel synthetic approach to aculeatin A via a stepwise strategy. Abstract : Aculeatin A, isolated from the plant Amomum aculeatum, is a dispirocyclic compound having antimalarial activity. In this paper, we describe a novel synthetic approach to aculeatin A from 1-tetradecanal in nine steps via a stepwise strategy. The key features of this approach include the 1, 3-diketone preparation from Claisen condensation of ketone and acyl chloride, cyclodehydration, and intramolecular oxa-Michael addition to 2, 3-dihydro-4 H -pyran-4-one.